SEG Technical Program Expanded Abstracts 2013 2013
DOI: 10.1190/segam2013-1277.1
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic search engine

Abstract: Similar to a web search engine, we develop a microseismic search engine that can help to estimate event location, magnitude, and focal mechanism all together in less than a second. The method includes the calculation of all possible microseismic events over a 3D grid with a known velocity model. We then index and rank all of the seismic waveforms following the characteristics of phase and amplitude information and create a database by applying multiple randomized K-dimensional tree method. When a microseismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The MapReduce model was proposed by two engineers at Google, who observed that many massively parallel processing operations, implemented for the needs of their search engine, followed an identical parallelization strategy. From these observations was born the MapReduce programming model, first described in 2004 [16]. The Map inspires his processing abstraction and Reduce primitives present in many functional languages like Lisp.…”
Section: Mapreduce Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…The MapReduce model was proposed by two engineers at Google, who observed that many massively parallel processing operations, implemented for the needs of their search engine, followed an identical parallelization strategy. From these observations was born the MapReduce programming model, first described in 2004 [16]. The Map inspires his processing abstraction and Reduce primitives present in many functional languages like Lisp.…”
Section: Mapreduce Paradigmmentioning
confidence: 99%
“…In this paper, we propose a parallel implementation to address this problem. A proven effective parallel computing paradigm is MapReduce [16]. It is a massively parallel programming model suitable for processing very large amounts of data.…”
Section: Introductionmentioning
confidence: 99%